Glioma-associated protein CHI3L2 suppresses cells viability and induces G1/S transition arrest - Avdieiev, S.S.; Gera, L.; Hodges, R.; Dmytrenko, V.V. (Вiopolymers and Cell, 2015)
Aim. To analyze the effect of the CHI3L2 protein on malignant and non-malignant cell viability, and determined the CHI3L2 impact on the cell cycle and signaling pathways involved in the cell cycle regulation. Methods. MTT-based cell proliferation assay, FACS, western blot analysis. Results. The CHI3L2 protein inhibits the glioma cells viability and potentiates the effect of anti-cancer cytotoxic agents. The CHI3L2 treatment results in the G1/S transition arrest. CHI3L2 provoked a dramatic reduction of pRB phosphorylation and a significant decrease in the cyclin D1 expression, whereas the p53 and p21 expression levels were substantially increased. Conclusions. The CHI3L2 protein, which is overexpressed in human gliomas, is a negative regulator of the glioma cells viability. The reduced cell viability after the CHI3L2 treatment could be due to the activation of pRB and p53 and the downregulation of cyclin D. Мета. Проаналізувати життєздатність злоякісних та незлоякісних клітин за дії протеїна CHI3L2, а також визначити вплив CHI3L2 на клітинний цикл і сигнальні шляхи, залучені до його регуляції. Методи. МТТ–тест, проточна цитофлуориметрія, вестерн блот аналіз. Результати. CHI3L2 пригнічує життєздатність клітин гліоми людини і підсилює дію протиракових цитотоксичних агентів. CHI3L2 інгібує перехід клітин із G1- до S-фази клітинного циклу. CHI3L2 зумовлює зниження кількості фосфорильованої форми pRB, зменшення вмісту цикліну D1 та зростання вмісту p53 і p21. Висновки. CHI3L2, що надекспресується в гліомах людини, є негативним регулятором життєздатності клітин гліоми. Цитотоксичний вплив CHI3L2 може бути пов'язаним з активацією pRB та р53, а також зниженням вмісту цикліну D. Цель. Проанализировать жизнеспособность злокачественных и незлокачественных клеток при воздействии протеина CHI3L2, а также определить влияние CHI3L2 на клеточный цикл и сигнальные пути, вовлеченные в его регуляцию. Методы. МТТ-тест, проточная цитофлуориметрия, вестерн блот анализ. Результаты. CHI3L2 подавляет жизнеспособность клеток глиомы человека и усиливает действие противораковых цитотоксических агентов. CHI3L2 ингибирует переход клеток с G1- в S-фазу клеточного цикла. Влияние CHI3L2 приводит к снижению количества фосфорилированной формы pRB, уменьшению содержания циклина D1 и увеличению содержания p53 и p21. Выводы. CHI3L2, оверэкспрессия которого характерна для глиом человека, является негативным регулятором жизнеспособности клеток глиомы. Цитотоксическое влияние CHI3L2 может быть связано с активацией pRB и р53, а также снижением содержания циклина D.